Factors influencing responsible behaviour related to safety and health on mountains: A case study of climbers on Mount Kinabalu, Malaysia / Mahdi Esfahani - Esfahani, Mahdi (2014)
In mountaineering tourism, safety and health are pertinent aspects for both climbers and service providers. The climbers’ behaviours largely determine the favourable or unfavourable outcomes of their activity. Using the Theories of Planned Behaviour and Expectation Disconfirmation, this study examines the relationships between personality, spirituality, satisfaction, attitude towards behaviour, norms and perceived behavioural control with responsible behaviour and loyalty intention among climbers on Mount Kinabalu in Borneo. The questionnaire comprised of six sections which are demographic profile, responsible mountaineering behaviour, attitude, subjective norm, perceived behavioural control, satisfaction, loyalty intention, personality and spirituality. A panel of experts established the content validity of the initial drafted questionnaire. It was then subjected to face validity, pre-tested on five respondents with mountaineering experience to evaluate the questions’ answerability. The researcher conducted the questionnaire’s pilot testing on 107 Mount Kinabalu climbers to select suitable items and to check their reliability in measuring the constructs. During the main data collection, a total of 916 climbers completed the questionnaires, immediately after completing their climb. The researcher carried out preliminary analysis, item-total correlation and Exploratory Factor Analysis (EFA), followed by Confirmatory Factor Analysis (CFA), to test the validity of the questionnaire in terms of convergent validity, fit indices, uni-dimensionality assessment, discriminant validity and construct reliability. A separate sample of 300 respondents was used to conduct the EFA, while the remaining sample of 616 was used for the CFA. iii The results showed a high mean score for responsible mountaineering behaviour indicating that climbers paid close attention to behaviour related to health and safety. There are four newly discovered responsible behaviour dimensions in the mountains, which were termed as ‘clothing requirement’, ‘food and drink requirement’, ‘obedience requirement’ and ‘equipment requirement’. This study also showed the importance of media and social norms in influencing climbers’ behaviour. Spirituality, knowledge and norms influenced responsible behaviour among climbers. In addition, attitude towards behaviour partially mediated the relationship between spirituality and responsible mountaineering behaviour. Loyalty intention influenced responsible mountaineering behaviour and personality influenced both satisfaction and attitude towards behaviour. Based on the study findings, the researcher discusses the knowledge, marketing and managerial implications. The two main knowledge contributions of this study are the four newly discovered dimensions of responsible mountaineering behaviour and the importance of knowledge dimension within the attitude construct in influencing responsible behaviour. Climbers are able to scale the mountain top without any technical skill and sophisticated equipment, and able to experience high altitude and cold weather in the tropical latitude. This could be used for marketing communication to attract prospective climbers. Study findings may direct the attention of the authority to the possible managerial implications in Mount Kinabalu National Park.